Administrative Management in the Implementation of School Administrative Services at SMKN 1 Gowa - Arni Nasira; Sirajuddin Saleh; Sitti Hardiyanti Arhas (Journal of Educational Development and Learning (JEDAL), 2025)
Learning facilities have a major role in improving the quality of learning. Adequate facilities can create This study aims to determine the description of administrative management in carrying out school administration services at SMKN 1 Gowa. This study focuses on planning, organizing, implementing, and supervising school administration services. The research instruments used are observation and interview guidelines. The data collection technique employed in this study involves testing for data validity through credibility assessment. The data obtained were analyzed using the Miles, Huberman, and Saldana analysis model. Based on the results of the study, it shows that administrative management in carrying out administrative services at SMKN 1 Gowa is in a "fairly good" condition. This can be seen from the aspects of (1) administrative planning in carrying out school administration services by recruiting administrative staff, formulating the division of tasks and obligations of each staff member, and procuring any resources needed during the implementation. (2) Organizing administration in carrying out school administration services by determining the distribution of facilities and infrastructure that will later support the implementation of administrative management and creating a detailed concept for the mechanism for dividing administrative staff tasks. (3) Implementation of administration in running school administration services by carrying out or fulfilling planned activities and identifying what things need to be paid attention to in the process of implementing these activities. (4) Supervision of administration in running school administration services by confirming the preparation and implementation of tasks carried out and carrying out monitoring every two months or per semester to find out what obstacles there are during the implementation process.